Prevalence and factors related to fast food consumption among Mutah University Students, Jordan - Nesrin Riad Mwafi; Israa Mohammad Al-Rawashdeh; Waqar Abdul-Qahar Al-Kubaisy; Waleed Rifaat Ezzat; Raghad Abdelqader Al-Qazaqi; Mohamed Hashem Salameh (Journal of the Pakistan Medical Association, 2021)
Objective: To identify the prevalence and factors related to fast food consumption among Mutah University students in Jordan. Methods: A cross-sectional study was conducted during the period from January-April, 2019. A sample of 503 students was recruited from different faculties. The participants were interviewed using a structured and a validated questionnaire. Height and weight were measured for the Body Mass Index (BMI) calculation. Statistical analyses were performed using descriptive, t-test and correlational methods. Results: The prevalence of regular fast food (RFF) consumption (³ 2 times/week) was 59.4%. This prevalence was significantly higher among students spending ³ 21 JD/ week (p= 0.020) and those who were not performing physical exercise (p = 0.025). Significant correlations were found between RFF consumption and fried potato (r=0.374, p < 0.001), processed meat products (r=0.509, p < 0.001), coffee (r=0.122, p=0.006) and candies (r=0.092, p=0.039). No significant relation was found between fast-food consumption and BMI, religion, gender, field of study or living away from family. The most common reason for RFF consumption was shortage of time (38.5%). Lunch time was the most preferred time to consume fast food (70.2%). Interestingly, 32.4% of the students were willing to read the nutrient information and about two-thirds were interested to choose healthy meals if they were available in the menu. Conclusion: The prevalence of fast food consumption is high. RFF consumption is significantly related to lower physical exercise performance and the amount of pocket money. Raising awareness of university students through nutritional education is highly recommended. Continuous...